On dilatons and the LHC diphoton excess - Megias, Eugenio; Pujolas, Oriol; Quiros, Mariano [UNESP] (Springer, 2016)
We study soft wall models that can embed the Standard Model and a naturally light dilaton. Exploiting the full capabilities of these models we identify the parameter space that allows to pass Electroweak Precision Tests with a moderate Kaluza-Klein scale, around 2 TeV. We analyze the coupling of the dilaton with Standard Model (SM) fields in the bulk, and discuss two applications: i) Models with a light dilaton as the first particle beyond the SM pass quite easily all observational tests even with a dilaton lighter than the Higgs. However the possibility of a 125 GeV dilaton as a Higgs impostor is essentially disfavored; ii) We show how to extend the soft wall models to realize a 750 GeV dilaton that could explain the recently reported diphoton excess at the LHC.
Keywords: Phenomenology of Field Theories in Higher Dimensions; Phenomenology of Large extra dimensions